SAT0094 Celecoxib does not increase the risk of cardiac failure, oedema, or hypertension compared to nsaids: results from success 1, a double blind, randomised trial in 13, 274 oa patients. (1st June 2001) - Whelton, A; Singh, G; White, W; Fort, J; Bello, A
Abstract : Background: COX-2 specific inhibitors have been shown to significantly reduce the risk of gastrointestinal complications compared to conventional NSAIDs, while providing equivalent efficacy. However, some recent studies have raised concerns about the cardiovascular and renal safety profile of COX-2 inhibitors. In a previous study of 7, 968 patients in North America, celecoxib at supratherapeutic doses (800 mg/d) was shown not to increase the risk of hypertension, congestive heart failure, or renal adverse events compared to therapeutic doses of ibuprofen and diclofenac. Objectives: To compare the risk of congestive heart failure, oedema, and hypertension in OA patients treated with celecoxib at 200 or 400 mg per day compared to patients taking therapeutic doses of diclofenac and naproxen in a multinational, double-blind randomised trial (SUCCESS-1 in OA). Methods: A total of 13, 274 patients from 1142 sites in 39 countries in Europe, South Africa, Asia, Latin America, and the United States and Canada were enrolled in the SUCCESS-1 trial. Patients were randomly assigned to fixed treatment regimens of celecoxib 200 mg per day, celecoxib 400 mg per day, or NSAIDs (naproxen 1000 mg per day in the US and Canada and diclofenac 100 mg per day in other regions). Results: Of the 13, 194 patients randomised, 4421 and 4429 patients received 200 or 400 mg per day of celecoxib respectively, 914 patients received 1000 mg per day of naproxen, and 3510 patients received 100 mg per day of diclofenac. Patients were mostly female (67%), and 42% were 65 years or older (mean age: 62 years). Previous cardiovascular disease was comparable in each intent-to-treat group (p = 0.25). ASA use was 7.9% and 8.0% at baseline, in the celecoxib and NSAID groups, respectively. The number of patients with cardiovascular and renal events adverse events is shown in the Table 1 below: Conclusion: SUCCESS 1 provides additional evidence that celecoxib is associated with low incidence of cardiovascular or renal toxicity that is comparable to conventional NSAIDs. Sponsored by Pharmacia Corporation and Pfizer Inc.